Study of Potential Extension For Improving Knowledge Society in Ngadas Village about Medicinal plants - hajmia guswika (Yogyakarta State University, 2017)
Society knowledge in Ngadas village about medicinal plants began to fade, as people do not know the plants that can be consume as a drug around them. However, the treatment by plant utilizing is a traditional medicine that has become a cultural heritage that should be conserved and has been recommended by the WHO as the effort back to nature for the maintenance of public health, prevention and treatment of disease. Wild plant that has potential as a drug in the village Ngadas big enough examples adas, ajeran, akasia duri, anting-anting, alang-alang, patikan kebo, pegagan, semanggi gunung, kersen, krisan, kecubung gunung, tempuyung, etc. The purpose of writing this article is to examine the potential of extension as a efforts on improving knowledge of society. The method used is to review literature of some journal that examines the educational efforts to improve public knowledge. Based on data obtained from reviewing the literature, extension activities proved potentially in increasing knowledge of society. Thus it is needed to do extension in an effort to provide information on the potential of medicinal plants in the Ngadas villages.